The critical external heat source conditions for subcritical ORC system based on thermo-economics - Xiao, Lan; Wu, Shuang-Ying; Li, Chun (Journal of mechanical science and technology, 2016)
Considering the thermodynamic and economic constraints simultaneously, the critical external heat source conditions available for sub-ORC systems with pure or zeotropic mixture working fluids are clarified. The critical external heat source conditions include the maximum allowed heat source temperature T gi,max , the minimum allowed heat source temperature T gi,min and the minimum allowed heat source mass flow rate m g,min . The results show that, no matter using pure working fluid or zeotropic mixture working fluid, the maximum allowed heat source temperature T gi,max increases linearly with the increasing of its critical temperature T cr . For the pure working fluid, the minimum allowed heat source temperature T gi,min is not sensitive to the variation of T cr . While, for the zeotropic mixture working fluid, the minimum allowed heat source temperature T gi,min firstly falls down, then rises up along with the increasing of T cr . An increase in mass flow rate of heat source causes enlarged range of heat source temperature available. And the minimum allowed heat source mass flow rate m g,min reduces sharply with the increase of heat source temperature.